Does Islamic Financial Foster Economic Growth? Evidence from Indonesia - Ariyani, Diyah; Juwita Mega Rosita; Heri Kurniawan; Anisa Dewi Arismaya; Muhammad Soliki Ariwoto (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The purpose of this study was to determine the effect of Third-Party Funds (X1), Financing (X2), FDI and PMDN Investment Realization (X3) and Exchange Rates (X4) on Economic Growth (Y). This type of research is quantitative research with Error Correction Model (ECM) as a method of data analysis using secondary data in the form of time series. The data used is quarterly data from Third Party Funds, Financing, Investment Realization (FDI and PMDN), Exchange Rates and Gross Domestic Product (GDP) for 2013-2022. The data obtained were 40 samples which were then analyzed using the E-views 12 tool. Based on the results of this study indicate that partially the dependent variable Third Party Funds in the short term and long term has a positive and insignificant impact. Financing has a significant positive effect in the long term, Exchange Rate has a positive and significant effect, Investment Realization (FDI and PMDN) in the short and long term has a positive and significant effect on Indonesia's Economic Growth as indicated by the Gross Domestic Product (GDP) in 2013-2022.